Thermal, spectroscopic and DFT studies of solid benzamide - Perpetuo, Glauco Lini; Gálico, Diogo Alves; Guerra, Renan Barrach; Moreira, Ralph; Chierice, Gilberto Orivaldo; Bannach, Gilbert [UNESP] (My University, 2014)
Thermogravimetry (TG), differential thermal analysis (DTA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), and DFT theoretical calculations were used to study benzamide. The TG-DTA and DSC curves provided information concerning the melting point, evaporation and thermal stability of the compound. Using the FTIR technique it was possible to confirm the evaporation of the compound with no degradation. Density functional theory (DFT) at the 6-311++G (3df, 3dp) level, provided information regarding the energies involved in HOMO-LUMO transitions and the chemical stability of the compound.
Keywords: Benzamide; Evaporation; FTIR; TG-DTA; DSC